The impact of the conflict in Ukraine on the stability of the international system - Geremet, Assistant Prof Khaled Hamza (The International and Political Journal, 2023)
Since the emergence of the great empires, they have been fighting among themselves to extend their influence and prove their hegemony and tighten their grip to lead and control the world according to their own interests, and this scene is repeated with the change of competing poles of great power, and the conflict that we are witnessing during this stage is nothing but a translation of those conflicts that extend throughout history. Russia, after declaring war on Ukraine and occupying parts of it, especially Crimea, seeks to confront the American and European danger and limit its extension that threatens the Russian Empire as a superpower. Urgent solutions are provided.